Children as Mathematicians: The Interplay between Discourse Structure, Mathematicising, and the Participatory Approach. (22nd January 2012) - Kaartinen Kaartinen, Sinikka Sinikka; Latomaa Latomaa, Timo Timo
Abstract : This paper investigates the discourse structure, mathematicising and the participatory approach in an early education classroom community whose pedagogy in the learning of mathematics draws on the sociocultural perspective. The social interactions of the classroom community, as well as the role of pre-symbolic sign vehicles as semiotic tools in supporting interaction building, mathematicising, and strategy selection, were subjected to a qualitative micro-level analysis based on applied discourse and semiotic procedures. The results of the study suggest that the young children's mathematical ability develops during the two-year observation period from nonverbal participation to verbal participation through the following core elements: attention to numeracy, the learning of number words, object counting and mathematical story telling. The iconic and indexical pre-symbolic sign vehicles and semiotic chaining applied in the learning situations provide the learning community with the means to structure their experiences of their everyday practise and to relate them to the culture of mathematicising.